Macrocrack propagation in a notched shaft segment of human long bone: Experimental results and mechanical aspects. (April 2022) - Tailhan, J.-L.; Kurtz, T.; Godio-Raboutet, Y.; Rossi, P.; Thollon, L.
Abstract: Experimenting with crack propagation in human cortical tissue is a necessary prerequisite for developing a cracking model. A three-point bending test on a shaft section of a notched human long bone is presented. A procedure for carrying out the experimental test, including unloading/reloading cycles, is implemented. The results obtained are analyzed regarding the physical mechanisms which occur in the different phases of the test, and during the cycles. The prominent role of cracking is highlighted. In addition a hypothesis is proposed concerning the potential effect of initial internal residual stresses, due to bone remodelling, on the significant residual notch openings after unloading and on the cycles' shape. Highlights: A crack propagation test performed on a shaft segment of a human femur. An experimental test controlled with a low rate of notch opening displacement to maintain a stable crack propagation. An procedure with unloading/reloading cycles to assess the effect of cracking processes on the structural response. Results and analysis highlight the prominent role of cracking on the global behavior as well as on the cycles' shapes. A hypothesis on the role of internal "residual" stress relaxation on residual displacements amounts and cycle hysteresis.